Reception Mechanisms of Anton Pann’s Work in Cosmin Ciotloș’ Book, Anton Pann. Până când nu te iubeam - Horonceanu-Bernevic, Tincuta (Acta Universitatis Danubius. Communicatio, 2024)
The mechanisms of reception of Anton Pann’s work have been researched over time by historiographers of the time. In 2024, Cosmin Ciotloș’s book, Anton Pann. Until I Didn’t Love You, comes to bring a new breath to this chapter, namely, the author proposes a reconstruction of the life of the great Anton Pann, through a tangled story based on an accusation of plagiarism. This accusation came thirty years after the poet’s death. The novelty of the story lies in the fact that the author, due to the lack of precise biographical data, proposes an imaginary character, Ștefan Valentineanu, who, meticulously, focuses on the accusation of plagiarism, trying to uncover the truth. This character is a rigorous guy, a colleague of Spiru Haret, a lonely scholar, an archivist at the Academy Library. The story itself is enjoyable not only for researching Anton Pann’s work, but also for a simple reader.